Kebijakan Dinas Pendidikan Provinsi Sulawesi Tengah dalam Mengembangkan Kompetensi Guru Mata Pelajaran Produktif SMK Di Kota Palu - Rustam Efendi; Lukman Nadjamuuddin; Idrus A Rore; Nuraedah Nuraedah (Universitas Indraprasta PGRI, 2026)
The objectives of this study are: 1) to analyze policies regarding the development of vocational high school teachers’ competencies in Palu City; 2) to analyze the factors influencing the Central Sulawesi Provincial Education Office’s policies regarding the development of vocational high school teachers’ competencies in Palu City; and 3) to analyze the effectiveness of the Central Sulawesi Provincial Education Office’s policies regarding the development of vocational high school teachers’ competencies in Palu City. The research method employed a qualitative approach with data collection techniques including in-depth interviews, observation, and documentation. Data analysis consists of: data collection, data reduction, data display, and interpretation or drawing research conclusions. Based on data analysis and discussion of the research results, it is concluded that: 1) the Central Sulawesi Provincial Education Office has implemented various policies to develop the pedagogical and professional competencies of vocational high school (SMK) vocational subject teachers in Palu City, including through programs such as: the provision of master’s degree scholarships, OGN, and various workshop, training, and technical guidance programs that strengthen the pedagogical and subject-specific competencies (Tefa) of vocational high school (SMK) teachers of productive subjects in Palu City; 2) The policies of the Central Sulawesi Provincial Education Office in developing the competencies of vocational high school (SMK) teachers of productive subjects in Palu City are influenced by various factors, namely: a) Actor Factors; b) System Factors; and c) Infrastructure Factors; and 3) It was objectively concluded that the policy of the Central Sulawesi Provincial Education Office regarding the development of vocational high school teachers’ competencies in Palu City has not yet reached the “Good” qualitative rating, but it is also not in the “Poor” category; rather, it is categorized as “Fairly Good.”